Morphological Characteristics Of Cocos nucifera L. Origin Bone And Selayar District, Sulawesi Selatan - Kurnia Makmur (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2021)
Selayar Islands Regency is one of the coconut (Cocos nucifera L.) producing centers in South Sulawesi. C. nucifera from this area is one type of coconut that fills the market spread across several areas in South Sulawesi. Coconut character as a determinant of consumer attractiveness. In addition, the character of a plant can be used as a step in conservation, cultivation, and germplasm efforts. One solution is to characterize the morphology of these plants. This study aims to analyze and determine the morphological characters of C. nucifera from Bone Selayar Islands district. This research was conducted in the mountainous area of ​​Bone Regency and the coastal area of ​​Selayar Islands Regency. The coconut plant samples observed were deep type coconut plants (C. nucifera L. var typical). Each area was observed as many as 10 accessions of C. nucifera which were randomly selected in the farmer's. The object of the analysis used a descriptive method based on the International Plant Genetic Resources Institute (IPGRI) coconut descriptor manual (International Plant Genetic Resources). The sampling technique was carried out by accidental sampling. Morphological characters C. nucifera observed were tree height, stem diameter, number of fruits, fruit size, and leaf color. The results showed that coconut plants from Bone and the Selayar Islands generally had almost the same morphological characters, the only difference